1991
DOI: 10.1111/j.1749-6632.1991.tb00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Energy Metabolism in Alzheimer's Disease Studied with PETa

Abstract: Positron emission tomography (PET) is currently the only technology affording three-dimensional measurement of the brain's energy metabolism which is closely coupled to brain function. Studies of glucose metabolism by PET of (18F)-2-fluoro-2-deoxy-D-glucose are therefore widely applied to show the contribution of various brain structures in the performance of a variety of tasks or their participation in functional deficits associated with various diseases. Although glucose metabolism decreases slightly with ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 19 publications
4
66
0
2
Order By: Relevance
“…However, no significant differences were noted between group 5 and any of the other groups. This may support the previous consensus [34,35] that the primary sensory, motor and visual cortices, occipital region, basal ganglia, cerebellum, thalamus and brainstem are largely spared the ravages of AD.…”
Section: Discussionsupporting
confidence: 79%
“…However, no significant differences were noted between group 5 and any of the other groups. This may support the previous consensus [34,35] that the primary sensory, motor and visual cortices, occipital region, basal ganglia, cerebellum, thalamus and brainstem are largely spared the ravages of AD.…”
Section: Discussionsupporting
confidence: 79%
“…Single photon emission computed tomography (SPECT) and positron emission tomography (PET) studies have revealed decreases in blood flow and glucose metabolism that are relatively greater in temporal and parietal than in frontal lobes, and that tend not to extend to primary sensory areas . Ratios between metabolic rates in major brain areas discriminated better between AD patients and controls than did the metabolic rate in a single area [23,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Piracetam activates brain adenylate kinase and produces a significant increase in the cerebral glucose utilisation in the whole brain of rats 21 Also in man, an increase in glucose utilisation was observed 22 . Piracetam has also been observed to increase the blood flow in some situations, probably because of decreased platelet aggregation, enhancement of red blood cell deformability and reduction in adherence of damaged erythrocytes to endothelial cells 23 .…”
Section: Observations and Resultsmentioning
confidence: 99%